A gallery of chaotic systems with an infinite number of equilibrium points. (December 2016) - Pham, Viet–Thanh; Jafari, Sajad; Volos, Christos; Kapitaniak, Tomasz
Abstract: In this work, a systematic search for finding chaotic systems with infinite equilibria is described. As a result, we obtained a gallery of chaotic systems with various shapes of equilibrium points such as a line, two parallel lines, a piece–wise linear curve, a parabola, a hyperbola, or a circle. Interestingly, such novel systems exhibit "hidden attractors", which play vital roles in nonlinear theory and practical engineering issues.